Amorphous flexible covalent organic networks containing redox-active moieties: a noncrystalline approach to the assembly of functional molecules. Issue 27 (17th June 2020) - Suzuki, Jumpei; Ishizone, Akira; Sato, Kosuke; Imai, Hiroaki; Tseng, Yu-Jen; Peng, Chi-How; Oaki, Yuya
Abstract : Amorphous flexible covalent organic networks containing functional molecules were synthesized by consecutive and multiple reactions at different rates and in multiple directions. Abstract : The organization states of functional molecules have a significant impact on the properties of materials. A variety of approaches have been studied to obtain well-organized molecular assemblies. The present work shows a new non-organized state of isolated and dispersed functional molecules in amorphous flexible covalent organic networks. Redox-active quinone molecules are embedded in the amorphous network polymers. Consecutive reactions between benzoquinone (BQ) and linker molecules generate random network structures through polymerization at different rates and in multiple directions. The low-crystalline stackings of the amorphous network polymers facilitate the formation of nanoflakes through exfoliation in dispersion media. Enhanced electrochemical performances, one of the highest specific capacities in recent studies, were achieved by efficient redox reactions of the quinone moiety. The present noncrystalline approach, low-crystalline stacking of designer amorphous covalent organic networks, can be applied to construct similar nanostructured polymer materials containing functional units.